Identification and Characterization of Genes Involved in Benzylisoquinoline Alkaloid Biosynthesis in Coptis Species - He, Si-Mei; Liang, Yan-Li; Cong, Kun; Chen, Geng; Zhao, Xiu; Zhao, Qi-Ming; Zhang, Jia-Jin; Wang, Xiao; Dong, Yang; Yang, Jian-Li; Zhang, Guang-Hui; Qian, Zhi-Long; et al. (Frontiers in Plant Science, 2018)
The dried rhizomes of Coptis chinensis have been extensively used in heat clearing, dampness drying, fire draining, and detoxification by virtue of their major bioactive components, benzylisoquinoline alkaloids (BIAs). However, C. teeta and C. chinensis are occasionally interchanged, and current understanding of the molecular basis of BIA biosynthesis in these two species is limited. Here, berberine, coptisine, jatrorrhizine, and palmatine were detected in two sepecies, and showed the highest contents in the roots, while epiberberine were found only in C. chinensis. Comprehensive transcriptome analysis of the roots and leaves of C. teeta and C. chinensis respectively identified 53 and 52 unigenes encoding enzymes potentially involved in BIA biosynthesis. By integrating probable biosynthetic pathways for BIAs, the jatrorrhizine biosynthesis ill-informed previously was further characterized. Two genes encoding norcoclaurine/norlaudanosoline 6-O-methyltransferases (Cc6OMT1 and Cc6OMT2) and one gene encoding norcoclaurine-7OMT (Ct7OMT) catalyzed enzymatically O-methylate (S)-norcoclaurine at C6 that yield (S)-coclaurine, along with a smaller amount of O-methylation occurred at C7, thereby forming its isomer (isococlaurine). In addition, scoulerine 9-OMT (CtSOMT) was determined to show strict substrate specificity, targeting (S)-scoulerine to yield (S)-tetrahydrocolumbamine. Taken together, the integration of the transcriptome and enzyme activity assays further provides new insight into molecular mechanisms underlying BIA biosynthesis in plants and identifies candidate genes for the study of synthetic biology in microorganisms.